MACHINE TRANSLATION: SANSKRIT TO ENGLISH - RAMESH, NIKHIL; KHANNA, SHREYA; BRISKILAL, J (International Journal of Psychosocial Rehabilitation, 2020)
Translation is the key for communication among countries on a global scale. Machine translation is the process of translating the source language to the target language performed by a computer. Machine translation can be performed by applying a variety of techniques or approaches each of which has its own set of benefits and disadvantages.This paper proposes to perform machine translation from Sanskrit to English. The development of the machine translation system for Sanskrit, being an ancient language is a challenging task. Sanskrit is one of the oldest languages in the world and is now not widely in use, yet a large number of ancient texts are written in the language and hence a translation system will prove to be crucial in their translation and understanding. This paper proposes to incorporate the Paninian f r a m e w o r k i n t o a n e u r a l machine t r a n s l a t i o n system